Lamprey 3D single-cell transcriptomics reveals ancestral and specialized features of the vertebrate brain - Haixu Wu; Duoyuan Chen; Jun Li; Tao Zhou; Zhenkun Zhuang; Zhiwei Niu; Zeyu Du; Yongjie Chen; Shunqin Chuan; Chunyan Xu; Xun Liao; Xiaoyu Meng; et al. (Science, 2026)
The lamprey occupies a pivotal position for elucidating vertebrate brain evolution. Using spatial transcriptomics and single-nucleus RNA sequencing, we generated a three-dimensional molecular atlas of the lamprey brain, identifying 209 distinct cell clusters across 14 regions. Cross-species comparisons revealed broad conservation of regional spatial architecture, defining an ancestral organizational blueprint. Within this conserved framework, however, marked lineage-specific divergence emerged. We observed extensive neuronal specialization across vertebrate lineages, accompanied by regulatory shifts associated with spatial reorganization and functional diversification of neuronal populations. Additionally, our results suggest that a cerebellum-like architecture predates the jawed vertebrate cerebellum. Together, these findings identified constraints on neural organization and detected cellular innovations driving evolutionary diversification.